The effect of diminazene, an angiotensin‐converting enzyme 2 activator, on adenine‐induced chronic kidney disease in rats. (7th November 2022) - Abdelrahman, Aly M.; Ali, Badreldin H.; Ali, Haytham; Manoj, Priyadarsini; Al‐Suleimani, Yousuf
Abstract: The present study investigated the effect of diminazene, lisinopril, or valsartan on adenine‐induced chronic kidney disease (CKD) in rats. The animals were divided into five groups ( n = 6). The first and second groups received normal diet and adenine in the feed at a dose of 0.25% w/w for 35 days, respectively. The third, fourth, and fifth groups were treated as the second group but also received diminazene (15 mg/kg/day), lisinopril (10 mg/kg/day), and valsartan (30 mg/kg/day), respectively, for 35 days. Adenine significantly increased plasma urea, creatinine, neutrophil gelatinase‐associated lipocalin (NGAL), calcium, phosphorus, and uric acid. In addition, adenine increased urinary albumin/creatinine ratio and N ‐Acetyl‐β‐ D ‐glucosaminidase (NAG)/creatinine ratio and reduced creatinine clearance. Adenine also significantly increased the plasma concentrations of inflammatory cytokines (plasma tumor necrosis factor–alpha [TNF‐α] and interleukin‐1beta [IL‐1β]) and significantly reduced antioxidant indices (catalase, glutathione reductase [GR], and superoxide dismutase [SOD]). Histopathologically, renal tissue from adenine‐treated rats showed necrosis of renal tubules, tubular casts, shrunken glomeruli, and increased renal fibrosis. All drugs ameliorated adenine‐induced biochemical and histopathological changes. The protective effect of the three drugs used is, at least partially, due to their anti‐inflammatory and antioxidant effects. Our results show that administration of diminazene, lisinopril, or valsartan had a comparable effect on the reversal of the biochemical and histopathological indices of adenine‐induced CKD in rats.